A homogenized XFEM approach to simulate fatigue crack growth problems. (1st April 2015) - Kumar, Sachin; Singh, I.V.; Mishra, B.K.
Highlights: A homogenization scheme based on strain energy density criterion is proposed to evaluate the effective properties. The homogenized XFEM approach drastically reduces the CPU time without compromising on the accuracy. Only 20% region (by volume) of the domain is selected for modeling the discontinuities near the major crack. The presence of multiple discontinuities significantly affects the fatigue life. The effect of holes is found more severe as compared to the minor crack and inclusions. Abstract: In this work, a homogenized XFEM approach has been proposed to evaluate the fatigue life of an edge crack plate in the presence of discontinuities (holes, inclusions and minor cracks). In this approach, the central 20% region of the plate is discretized by fine-mesh whereas remaining 80% region is discretized by coarse mesh. In case of holes and inclusion, the 80% continuum region of the plate has been modeled with homogeneous material properties. Special transition elements are developed to maintain the displacement continuity at the junction nodes. Several problems containing discontinuities in 20% region are solved by the proposed approach.